2008
DOI: 10.1038/sj.bjc.6604457
|View full text |Cite
|
Sign up to set email alerts
|

Inducible re-expression of p16 in an orthotopic mouse model of pancreatic cancer inhibits lymphangiogenesis and lymphatic metastasis

Abstract: Functional inactivation of the tumour suppressor protein p16 INK4a constitutes a key event in the multistep process of pancreatic ductal cell transformation. However, the significance of p16 inactivation for complex and tissue-specific aspects of pancreatic cancer progression, such as angiogenesis and metastasis, is less understood. Here, we inducibly re-expressed p16 in vivo in an orthotopic model of pancreatic cancer and examined the impact on these clinically relevant aspects of pancreatic cancer tumour bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
2
26
0
2
Order By: Relevance
“…45,46 Some authors have suggested that p16 INK4a plays a major role not only in suppression of cell division but also in suppression of lymphangiogenesis and lymphatic metastasis. 45 As far as we are concerned, the role of p16 INK4a immunoexpression as a marker for survival in PSCC has only been evaluated in 1 previous study and an association with a better overall survival was detected.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Some authors have suggested that p16 INK4a plays a major role not only in suppression of cell division but also in suppression of lymphangiogenesis and lymphatic metastasis. 45 As far as we are concerned, the role of p16 INK4a immunoexpression as a marker for survival in PSCC has only been evaluated in 1 previous study and an association with a better overall survival was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Following sequential transfection of pcDNA6/TR (cells described in ref. 30) and pcDNA4/TO-SP3xflag-SLIT2-mycHis, SLIT2 expression was induced by 1 mg/mL doxycycline (Sigma-Aldrich). Cells expressing pcDNA6/TR were used to exclude off-target effects of doxycycline.…”
Section: Generation Of Cell Clonesmentioning
confidence: 99%
“…In accordance to squamous cell carcinomas of other origins, we were able to demonstrate a more aggressive behavior of p16-negative tumors. Besides its impact in suppression of cell division, p16 seems to play a major role in suppression of lymphangiogenesis and lymphatic metastasis, since in vivo re-expression of p16 inhibited the process of lymphangiogenesis in pancreatic cancer [35].…”
Section: Discussionmentioning
confidence: 99%